2008
DOI: 10.1088/0960-1317/18/10/105004
|View full text |Cite
|
Sign up to set email alerts
|

Profile control of a borosilicate-glass groove formed by deep reactive ion etching

Abstract: Deep reactive ion etching (DRIE) of borosilicate glass and profile control of an etched groove are reported. DRIE was carried out using an anodically bonded silicon wafer as an etching mask. We controlled the groove profile, namely improving its sidewall angle, by removing excessively thick polymer film produced by carbonfluoride etching gases during DRIE. Two fabrication processes were experimentally compared for effective removal of the film: DRIE with the addition of argon to the etching gases and a novel c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In [18], it was shown that SiO 2 etching was increased by adding Ar for up to a certain value. However, including Ar to the gas chemistry may increase the physical etching due to ion bombardment and may contribute to increase in the sidewall angle [13]. In our experiment with the NLD plasma, we found that 10 to 50 sccm of Ar helped in reducing contamination on the etched surface because of the ion bombardment.…”
Section: B Gas Flowmentioning
confidence: 69%
“…In [18], it was shown that SiO 2 etching was increased by adding Ar for up to a certain value. However, including Ar to the gas chemistry may increase the physical etching due to ion bombardment and may contribute to increase in the sidewall angle [13]. In our experiment with the NLD plasma, we found that 10 to 50 sccm of Ar helped in reducing contamination on the etched surface because of the ion bombardment.…”
Section: B Gas Flowmentioning
confidence: 69%